Pengaruh Preferensi Masyarakat Kota Kupang terhadap Olahan Daging Babi - Tae, Maria Yohana Oy; Bhoko, Maria Sabina Theresia; Saka, Dulce Maria Gisela; Lian, Pemandi; Malut, Maria Goreti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to understand consumer preferences for processed pork in Kupang City. Through the survey, it was found that taste is the dominant factor influencing consumer choice, followed by product variation. Price is also a consideration, but service is less of a major focus. These results indicate that business actors need to focus more on developing taste and product variation to meet consumer needs. This study provides an important contribution to the development of the pork processed culinary industry in Kupang City.